2022
DOI: 10.1002/htj.22758
|View full text |Cite
|
Sign up to set email alerts
|

CFD analysis of a flat tube with semi‐circular fins using graphene nanofluid and to compare performance with square type of fins

Abstract: CFD analysis on a flat tube with semi‐circular fins under laminar flow conditions was performed with graphene‐based nanofluids considering the nanofluids as incompressible. Different simulations were performed at four different concentrations of nanofluids (0.01%, 0.1%, 0.2%, and 0.4%) and at different volume flow rates (4, 6, 8, and 10 LPM) and at four different forced convective heat transfer coefficients at different wind velocities at 300 K (50, 100, 150, and 200 W/m2 K). It was observed that with an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…With the use of experimental data and theoretical analysis, they also looked at the thermophysical characteristics of nanofluids and the effectiveness of heat sinks. Konni et al [ 17 ] focused on graphene-based nanofluids which are more effective than most nanofluids and observed that compared to base fluid, graphene-based nanofluid has a 200% improvement in thermal conductivity. An angular sector heat sink's mixed convection flow of nanofluid was statistically examined by Benkherbache and Si -Ameur [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…With the use of experimental data and theoretical analysis, they also looked at the thermophysical characteristics of nanofluids and the effectiveness of heat sinks. Konni et al [ 17 ] focused on graphene-based nanofluids which are more effective than most nanofluids and observed that compared to base fluid, graphene-based nanofluid has a 200% improvement in thermal conductivity. An angular sector heat sink's mixed convection flow of nanofluid was statistically examined by Benkherbache and Si -Ameur [ 18 ].…”
Section: Introductionmentioning
confidence: 99%